EFEKTIFITAS PENGGUNAAN VIDEO LEARNING DALAM MENINGKATKAN HASIL BELAJAR LABSKILL MAHASISWA KEPERAWATAN - Fitrianola Rezkiki; Sherly Amelia; Imelda Rahmayunia Kartika (HUMAN CARE JOURNAL, 2021)
Video Learning is one of the learning media that can be used in the laboratory to improve the lab skills of nursing students. The development of video learning focuses on developing practicum learning content and improving skills lab learning outcomes. The importance of video learning being applied in the laboratory to answer the industrial revolution 4.0 in the form of the use of digital technology for the educational aspect in the laboratory and the urgency in the midst of the Covid-19 pandemic. The purpose of this study was to find out how effective video learning is in improving nursing students' lab skills learning outcomes in the laboratory. The research method used is a quantitative approach, with a quasi-experimental type of research with a non-equivalent post-test only control group design experimental design. The population in this study were nursing students at the Faculty of Health, University of Fort De Kock. The research samples were students of the 2019 and 2020 batches which were taken with a sampling technique carried out by random sampling with a cluster sampling type of 160 students. Data analysis techniques include data normality test, homogeneity test and hypothesis test (t test). The results of this study showed that the average of skill lab learning outcomes of nursing students in the laboratory using video learning was 83.71, while the average skill lab learning outcomes of nursing students using conventional learning methods (demonstrations) was 78.32. There is a significant difference in learning outcomes (p-value 0.001) between lab skills learning using video learning compared to lab skills learning in the conventional way (demonstrations in the laboratory). It is expected that educators can further increase creativity in making attractive learning lab skills videos so as to increase interest in learning and learning outcomes for nursing students, especially in learning in the laboratory. Keywords: video learning, skill lab, learning outcomes, nursing students